Neurohormonal Profiles of Assistance Dogs Compared to Pet Dogs: What Is the Impact of Different Lifestyles? - Manuel Mengoli; Jessica L. Oliva; Tiago Mendonça; Camille Chabaud; Sana Arroub; Céline Lafont-Lecuelle; Alessandro Cozzi; Patrick Pageat; Cécile Bienboire-Frosini (Animals, 2021)
Assistance dogs must manage stress efficiently because they are involved in challenging tasks. Their welfare is currently a fundamental issue. This preliminary study aimed to compare assistance dogs (AD; n = 22) with pet dogs (PD; n = 24), using blood neuromodulator indicators to help find biomarkers that can improve the AD breeding, selection, training, and welfare monitoring. Both populations originated from different breeds, are of different ages, and had different lifestyles. Basal peripheral concentrations of prolactin (PRL), serotonin (5-HT), free (fOT) and total (tOT) oxytocin were measured by immunoassays. Multiple linear regressions were performed to assess the effect of activity, age, sex, and their interactions on these parameters. Correlations between neurohormonal levels were analyzed. No interactions were significant. fOT and tOT concentrations were significantly influenced by age (p < 0.0001 and p = 0.0002, respectively) and dogs’ activity (p = 0.0006 and p = 0.0277, respectively). A tendency was observed for age effect on PRL (p = 0.0625) and 5-HT (p = 0.0548), as well as for sex effect on tOT (p = 0.0588). PRL concentrations were heterogenous among AD. fOT and tOT were significantly but weakly correlated (Pearson’s r = 0.34; p = 0.04). Blood prolactin, serotonin, and oxytocin may represent biomarkers to assess workload and chronic stress-related responses in ADs and eventually improve their selection and training.